2002
DOI: 10.1126/science.1072221
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Poly(ADP-Ribose) Polymerase-1-Dependent Cell Death by Apoptosis-Inducing Factor

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) protects the genome by functioning in the DNA damage surveillance network. PARP-1 is also a mediator of cell death after ischemia-reperfusion injury, glutamate excitotoxicity, and various inflammatory processes. We show that PARP-1 activation is required for translocation of apoptosis-inducing factor (AIF) from the mitochondria to the nucleus and that AIF is necessary for PARP-1-dependent cell death. N-methyl-N'-nitro-N-nitrosoguanidine, H2O2, and N-methyl-d-aspartate ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

86
1,451
9
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,654 publications
(1,560 citation statements)
references
References 27 publications
86
1,451
9
14
Order By: Relevance
“…Another possibility is that AIF is not the alone effector of A3D8-induced cell death. Indeed, the phenotype of cell death described here was not identical to the previously identified AIF-induced cell death involving delayed cytochrome c release and subsequent caspase cascade (Susin et al, 1999;Yu et al, 2002). Thus, it is possible that death effectors other than AIF contribute to the caspase-independent cell death induced by A3D8.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Another possibility is that AIF is not the alone effector of A3D8-induced cell death. Indeed, the phenotype of cell death described here was not identical to the previously identified AIF-induced cell death involving delayed cytochrome c release and subsequent caspase cascade (Susin et al, 1999;Yu et al, 2002). Thus, it is possible that death effectors other than AIF contribute to the caspase-independent cell death induced by A3D8.…”
Section: Discussioncontrasting
confidence: 73%
“…Recent observations indicated that AIF may be a key molecule in PARP-1-mediated caspase-independent cell death (Yu et al, 2002;Hong et al, 2004). Although the mechanism of PARP-1-mediated release of AIF remains elusive, it appears to be involved in apoptotic forms of cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the apoptotic role of AIF following its release and translocation to the nucleus [3,[139][140][141][142], AIF also has a physiological Fig. 4 During excitotoxicity, elongated mitochondria along the neurite and at the synapse can buffer Ca 2+ more effectively than fragmented mitochondria.…”
Section: Mitochondrial Cristae Structure and Cell Death: Demolition Fmentioning
confidence: 99%
“…Taking advantage of a procedure involving the preferential conformation of cationic dye in mitochondria (alive cells) or in cytoplasm (apoptotic cells), we then examined the mechanism that underlies the marked reduction of cells number and the modifications of cell morphology caused by ABT-737. TFK-1 cells were treated with 30 µM ZOL and 10 µM ABT-737 alone or in combination (Fig.4A), while EGI-1 cells were treated with 15 µM ZOL and 3 µM ABT-737 alone or in combination (Fig.4B) Recently, a specific PARP-1 mediated caspaseindependent pathway of cell death leading to the translocation of the mitochondrial apoptosisinducing factor (AIF) via cytoplasm to the nucleus has been described [31]. To analyze the discrepancy between earlier PARP-1 activation in comparison to caspase cleavage in our cell lines, we then verified AIF releasing in the cytoplasm following ABT737 and/or ZOL exposure.…”
Section: Mitochondrial Depolarization Assessmentmentioning
confidence: 99%